Patient-Centered Neurosurgery: Improved Outcomes after Subtotal Surgical Resection and Nonframe-Based Fractionated Stereotactic Radiotherapy for Large Cerebellopontine Angle Vestibular Schwannoma - Hazra, Darpanarayan; Chandy, Gina Maryann; Roy, Sanjoy; Ghosh, Amit (Indian Journal of Neurosurgery, 2024)
Background The novel paradigm in neurosurgery for large vestibular schwannomas (VSs) involves a combination of planned subtotal resection (STR) and scheduled postoperative fractionated stereotactic radiotherapy (FSRT).Methods This retrospective observational study aimed to evaluate and compare the outcomes of patients who underwent either near-total resection (NTR) or were treated with STR and scheduled FSRT over 6 years. We systematically coded and analyzed the data to obtain comprehensive insights into the results.Results Our study included 65 patients diagnosed with large VS, who underwent retrosigmoid craniotomy and NTR or STR for tumor removal. The mean age of the cohort was 42.6 (standard deviation: 16.2) years, with 40 (61.5%) female patients. All patients presented with asymmetrical sensory neural hearing loss and other prevalent symptoms such as headache (58) and tinnitus (58). Cerebellar signs, speech abnormalities, and pyramidal signs were also observed. Ten patients underwent NTR, and 55 underwent STR followed by an FSRT at 3 months or later based on the physical and radiological findings. Facial nerve palsy was noted in all cases of those who underwent NTR, while no instances of facial nerve palsy, lower cranial nerve palsy, posterior fossa, or brain stem injury were noted in the STR group. One patient undergoing STR experienced meningitis and died despite best possible medical management. The majority of patients showed symptom improvement, and none of the patients reported recurrence at 3-year follow-up.Conclusion The combined approach of STR and FSRT ensures safety, high tumor control rates, and favorable outcomes. It provides a sensible alternative to NTR for managing large tumors, emphasizing tumor debulking while preserving neurological function for overall benefit.
Keywords: vestibular schwannoma; cerebellopontine angle; adjuvant stereotactic radiotherapy; subtotal resection; near-total resection; adaptive hybrid surgery